Examining tolerability, safety, and blinding in 1032 transcranial electrical stimulation sessions for children and adolescents with neuropsychiatric and neurodevelopmental disorders - Andrea Battisti; Giulia Lazzaro; Luciana Ursumando; Barbara D’Aiello; Valeria Zanna; Floriana Costanzo; Stefano Vicari; Deny Menghini (Scientific Reports)
Abstract The present study first extensively evaluated the tolerability, safety, and blinding of transcranial direct current stimulation (tDCS) and transcranial random noise stimulation (tRNS) in paediatric clinical populations, composed of 92 children and adolescents (54 females, age range: 8–17 years), involving 1032 sessions across neuropsychiatric (i.e., anorexia nervosa) and neurodevelopmental (i.e., attention deficit and hyperactivity disorder, developmental dyscalculia) conditions. It compared adverse events (AEs) occurrence between active and sham transcranial electrical stimulation (tES) conditions (i.e., 528 active vs. 504 sham sessions) as well as tDCS and tRNS (i.e., 772 tDCS sessions vs. 260 tRNS sessions), while considering demographic and emotional-behavioural factors. Results showed tES safety with no “moderate” or “severe” AEs reported; about 77% of sessions were AE-free, supporting tES use in these populations. Itching was the most common symptom, and active sessions were found to be more likely to induce AEs compared to sham sessions. Notably, tRNS had a higher AE likelihood than tDCS, possibly due to experimental differences. In the current study, demographic and emotional-behavioural variables did not significantly affect AEs. Blinding procedures were moderately effective, with about half of participants correctly identifying their condition. As indicated in prior studies, tRNS seems to better preserve blinding integrity. In conclusion, this study provides comprehensive insights into tES tolerability and safety in paediatric clinical populations, emphasizing the need for further AEs exploration in tES and blinding procedure refinement in future research.